2017
DOI: 10.5792/ksrr.17.022
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation of Isolated Posterior Cruciate Ligament Avulsion Fractures: Clinical and Functional Outcome

Abstract: PurposeThe posterior cruciate ligament (PCL) presents commonly with avulsion fractures of its tibial attachment. An avulsion fracture of the PCL, if not surgically fixed, may lead to secondary changes in the knee joint. Various fixation techniques have been explored with use of lag screws, steel wires, absorbable screws, suture anchors and straddle nails. The purpose of this study was to evaluate the clinical and functional outcome of open reduction and internal fixation of tibial avulsion injuries of the PCL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Most commonly, as a result of a motor vehicle accidents and especially motorcycle injuries, a dashboard injury occurs when a posterior directed force is applied to the proximal tibia when the knee is flexed. Therefore, PCL avulsion fractures are more frequently reported in China, India, and other countries where motorcycle transportation is more prevalent [7]. The second most frequent mechanism is sportsrelated trauma, in which the mechanism is knee hyperextension [1•].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, as a result of a motor vehicle accidents and especially motorcycle injuries, a dashboard injury occurs when a posterior directed force is applied to the proximal tibia when the knee is flexed. Therefore, PCL avulsion fractures are more frequently reported in China, India, and other countries where motorcycle transportation is more prevalent [7]. The second most frequent mechanism is sportsrelated trauma, in which the mechanism is knee hyperextension [1•].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…The wide range noted in the reported incidence can be attributed to variable clinical presentations, including asymptomatic PCL injury [6]. Despite the low incidence of PCL injuries, resulting instability and early degenerative changes can be debilitating to patients, which are mostly young males [7]. Although there are many case series published on the management and outcomes of PCL avulsion fractures, no optimal surgical management has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Various open or arthroscopic techniques have been described in the literature regarding fixation of PCL avulsion injuries by using lag screws, steel wires, absorbable screws, suture bridge, suture anchors and tightrope, but no one technique has been considered a gold standard. 8,9 In this study we are present our experience with fixation using ABS button (Arthrex) and tightrope. It has a wide surface area to achieve compression at fracture site.…”
Section: Figure 2: Classification Of Avulsion Fractures Of Pclmentioning
confidence: 99%
“…Zhu et al [6] reported the merits of high-strength suture fixation under arthroscopy for 18 cases of PCL avulsion injury, all of which were successful. Joshi et al [7] reported improvement in 14 cases of PCL avulsion fractures after performing open reduction and an internal fix, but this treatment is limited to patients with fractures that have just occurred and is not recommended for patients presenting to clinic late.…”
Section: Introductionmentioning
confidence: 99%